Teaching and learning used of Compass Approach in Teaching Higher Order Thinking Skills in Sciences Subject: Kaedah Kompas dalam Pengajaran dan Pembelajaran Kemahiran Berfikir Aras Tinggi Sains - Che Seman @ Sulaiman, Shamilati; Wahab, Amran (Jurnal Pendidikan Bitara UPSI, 2022)
Teaching Higher Order Thinking Skills (HOTS) has its own challenges and needs to be emphasized in the curriculum because it is one of the skills of the 21st century. HOTS are among the six main characteristics of pupils who are the aspirations of the Malaysian Ministry of Education to succeed at the global level. Therefore, pupils can improve their cognitive skills with the opportunity and space given to convey their ideas/views using more creative methods and not just memorizing like conventional methods. Therefore, the process of learning Science does not happen by rote learning, but instead requires the application of HOTS. So, through the Compass Method, pupils have the opportunity to generate and develop thoughts to enable them to make their thoughts visible and further enable them to understand, analyze and master problems/issues with elements of HOTS in evaluating and making decisions to obtain the best solutions. This quasi-experimental study examines the effectiveness of the Compass Method in improving HOTS among 32 primary school pupils. The effect of using this method was measured three times using the HOTS test, that is before the intervention (pre-test), after the intervention (post-test) and after three months of the intervention (post-extended test). The data was analyzed to obtain a percentage score. Findings show an increase in the percentage of pupils’ achievement in both postal tests. The implication is that the Compass Method has succeeded in helping pupils in several aspects, namely being a guide to pupils in answering questions/solving problems of HOTS; guide pupils to improve their thinking ability to a higher level; make the pupil a reflective, critical and creative thinker; produce pupils who are skilled in evaluating and making decisions. This study suggests that this method be applied together in the learning process of other core subjects in order to meet the country’s aspirations in producing outstanding pupils holistically.